Deficientes visuais e acessibilidade urbanística: interações entre direitos humanos e meio ambiente. - Guedes, Denyse Moreira (2015)
The right to accessibility is universal, fundamental, especially for the visually impaired, solidified the constitutional right to equality and regulated in Brazil in terms of urban accessibility, the Brazilian Standard 9050 of the Brazilian Association of Technical Standards (ABNT / NBR 2004). The accessibility is minimal and basic rule of citizenship, so that materialized to in article 227, § 2º and article 244 of the Brazilian Federal Constitution. To give effect to these and other constitutional provisions pertinent to accessibility, was published, among others, the Law nº. 6.938/81, 7.853/89, 9.045/95, 10.048/00, 10.098/00 and 10.257/2001, which also tried to ensure the visually impaired person some social integration. Those standards are based on the fundamental human rights enshrined in constitutional provisions and several infra-constitutional norms. The Convention on the Rights of Persons with Disabilities and its Optional Protocol, signed in New York on March 30, 2007, are incorporated into the Brazilian legal system by means of Decree nº 6.949 of 2009. It has been that it is the only treaty International human rights approved with a qualified quorum, confirming that the state should undertake all efforts to ensure accessibility, in order to promote the equality of all, in compliance with the foundations of the Republic, citizenship and human dignity. However, what still turns out is the existence of built environments and adapted without being subject to universal design, urban public policies exclusive and disordered urban planning measures affecting the mobility, accessibility and sustainability to public buildings and public parks, on public transport and their mutual interactions of the visually impaired. The comparative law has been central to certain bodies of law and the international experience directly influences many internal rules, technical and legal procedures. By comparing the existing systems in Portugal, Spain and Brazil, this study highlights the advance of some Brazilian cities on the accessibility of the visually impaired, above major cities of European countries, particularly capital, where this research was access. The research sought to draw a comparative framework, major advances in the Brazilian and international legislation related to the visually impaired. The proposals were limited to indicate the National Organization of the Blind of Spain (ONCE) as a source of funding to possibly necessary expenses in urban planning in these major cities; Furthermore, also highlighted was a Santos institution, ""Lar das Moças Cegas"" as a paradigm of the thesis, in view of what we have in our times in terms of accessibility for the visually impaired.